Experiences of using Electronic Medical Records among Patients from Ethnic Minority Backgrounds: A Rapid Review - Corey Adams; Reema Harrison; Alison Merchant; Narelle Arblaster; Tracey Bucknall; Kathleen Gray; Guncag Ozavci; Nilmini Wickramasinghe; Vicky Yuan; Elizabeth Manias (Patient Experience Journal)
This study explores the experiences of individuals from ethnic minority backgrounds using electronic medical records (EMRs) and identifies strategies to improve the inclusivity and usability of EMRs, aiming to reduce the digital divide in their access and use. A rapid review of the literature was conducted using Medline, Embase, and CINAHL databases to identify relevant studies published between 2010 and November 2023, with the assistance of a medical librarian. A total of 44 studies were included in the review, revealing significant disparities in EMR adoption and utilization among ethnic minority groups. Three key themes of inequality were identified: presentation of EMR and patient portal options, the registration and activation process, and the actual use of patient portals. While the review considered all elements of EMR systems, most published research focused specifically on patient portals. To address these disparities, a multifaceted approach is necessary, one that acknowledges linguistic diversity, enhances digital health literacy, and actively incorporates feedback from ethnic minority communities to improve EMR engagement.